A)¹₆ <--- to jest jedna szosta :)

a) ¹₆t²+¹₃k²t+¹₃tk²-k²t+¹₂²-¹₆tk²=

b) -(-a)+(-b)=

c) a-(-(-b))=

d) (a+b)x²+(a+b)x=

e) 4(a+b)(4a-2)-(2a-2b)²

f) (3k+7l-2)(2l-2k)=

plis i pamiętajcie ze + i - daje minus i ze minus i munus daje plus z góry dzikuje

1

Odpowiedzi

Najlepsza Odpowiedź!
2010-03-08T18:42:14+01:00
A) ¹₆t²+¹₃k²t+¹₃tk²-k²t+¹₂²-¹₆tk²=
=t[(1/6)t+(2/6)k²+(2/6)k²-k²+(1/4)-(1/6)k²]=
=t[(1/6)t+(4/6)k²-(1/6)k²-k²+(1/4)]=
=t[(1/6)t+(3/6)k²-k²+(1/4)]=t[(1/6)t-(1/2)k=t[(1/6)t+(1/2)k²(1/4)]

b) -(-a)+(-b)=a-b

c) a-(-(-b))=a-b

d) (a+b)x²+(a+b)x=(a+b)(x²+x)=x(a+b)(x+1)

e) 4(a+b)(4a-2)-(2a-2b)²=
(4a+4b)(4a-2)-(4a²-8ab+4b²)=16a²-8a+16ab-8b-4a²+8ab-4b²=
=12a²-8a+24ab-8b-4b²=4(3a²-2a+8ab-2b-b²)

f) (3k+7l-2)(2l-2k)=6kl-6k²+14l²-14kl-4l+4k=-8kl-6k²+14l²-4l+4k=
=(-2)(4kl+3k²-7l²+2l-2k)